Imposed Borders in a Balkan Landscape and Its Literary Impact: The vision of Christians and Greeks in Ismail Kadare’s Chronicle in Stone - Falangas, Andronikos (Zeitschrift für Balkanologie, 2010)
The region of Epirus is a typical example of the Balkan complexity. Divided between Greece and Albania following the partition of the Ottoman possessions at the end of the Balkan Wars in 1913, it is inhabited by a population that speaks Greek, Albanian or Vlach and declares allegiance to the Christian or the Muslim faith. This particular situation made this land the theater of ethnic tensions aggravated by a historical context of wars, occupations, and political conflicts in both Greece and Albania. The state of the tragic reality of Epirus poses the following questions: What is the role of the internationally recognized Albanian novelist, Ismail Kadare, born in that region? Does he submit his pen to an objective analysis or to a political cause? Does he contribute to the harmonious coexistence of all his compatriots or sustain long existing ethnic and politic rivalries? This paper serves this quest through an analysis of the Chronicle in Stone (Kronikë në gur), one of his best known writings first published in Albanian in 1971. The author concludes that Kadare’s novel does reflect a Balkan state of mind imbued by religious, ethnic, and even racial stereotypes, as well by gender traditionalisms typical of a patriarchal society.